Black refractory coating as well as preparation method and application thereof
By using a dense coating formed from perovskite-type black ceramics, iron-chromium spinel, silicon carbide, and refractory cement, the problems of easy oxidation, powdering, and cracking of existing black refractory coatings at high temperatures are solved, achieving high-temperature stability and energy-saving effect, making it suitable for industrial furnaces.
Patent Information
- Application Number
- CN202511262887.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-05
- Publication Date
- 2025-12-05
AI Technical Summary
Existing black refractory coatings are prone to oxidation, powdering, and cracking at high temperatures, have insufficient adhesion, and have complex preparation processes, making them difficult to promote and apply in industrial furnaces.
Using perovskite-type black ceramics, iron-chromium spinel, silicon carbide, and refractory cement as the main raw materials, a dense coating is formed through a specific preparation method, which improves the high-temperature stability, adhesion, and energy-saving effect of the coating.
Maintaining coating stability and adhesion at high temperatures reduces fuel consumption, improves furnace energy efficiency and lifespan, and lowers costs.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of coating materials, in particular to a black refractory coating and a preparation method and application thereof. BACKGROUND
[0002] In the high-temperature industry field, the furnace is the core equipment for energy conversion and material processing, and its energy efficiency level and service life directly affect the economic benefits and environmental friendliness of industrial production. At present, the commonly used light-colored refractory materials (such as alumina bricks, silica bricks, mullite bricks and ceramic fibers) are used as furnace linings in industrial furnaces. Although these light-colored refractory materials have good high-temperature resistance, they exhibit a series of defects during long-term service. First, the infrared emissivity of light-colored refractory materials is generally low (0.3-0.5), and the absorption and re-radiation of heat energy at high temperatures are insufficient, resulting in uneven heat distribution in the furnace, low heating efficiency of workpieces, and additional fuel consumption. Second, the porous ceramic materials are easily penetrated and corroded by high-temperature furnace gases (such as CO2, SO2 and alkali metal vapor), resulting in phenomena such as pulverization and spalling, which shortens the service life of the furnace lining. At the same time, the frequent cold and hot cycles of industrial furnaces can cause thermal stress concentration, making the light-colored furnace lining prone to cracking and exhibiting poor thermal shock stability.
[0003] To solve the above problems, researchers propose to apply a black inorganic refractory coating on the surface of the furnace lining to realize the "black body" modification of the inner wall of the furnace. The black coating usually uses oxide, carbide or perovskite ceramic materials, and the infrared emissivity can reach 0.8-0.95, significantly improving the radiation heat transfer efficiency of the furnace wall, and improving the furnace temperature uniformity and heat transfer performance. In addition, the dense structure of the black coating can effectively block the penetration of furnace gas, improve the oxidation resistance and corrosion resistance of the furnace lining; some coatings containing SiC or phosphate system can also buffer thermal stress and enhance thermal shock resistance. In industrial practice, the black refractory coating not only reduces fuel consumption by 5%-15%, but also reduces the emission of CO2 and NOx pollutants, which embodies significant energy-saving and environmental protection benefits. x
[0004] Although black refractory coating shows good application prospects, the existing system still has certain limitations. Some black pigments (such as Fe3O4, carbon black) will undergo phase transition or oxidation in an oxidizing atmosphere above 1000℃, resulting in lighter color or even failure; under the long-term service condition of 1200-1600℃, the coating is prone to pulverization, cracking and peeling, which limits the high-temperature stability. Secondly, due to the mismatch of the thermal expansion coefficient between the coating and the substrate, a large thermal stress will be generated under the condition of frequent temperature rise and fall of the furnace, which will reduce the adhesion of the coating and the insufficient thermal shock resistance. At the same time, the infrared emissivity of the black coating will decrease due to the sintering and grain growth of the microstructure under long-term high temperature, and the energy-saving effect will gradually weaken. On the other hand, the preparation and construction process of some coatings need to strictly control the atmosphere, and the process is complex and the maintenance cost is high; it is still difficult to be popularized and applied in conventional industrial furnaces. Based on this, it is of practical significance to develop a black refractory coating with excellent high-temperature stability, low cost and good energy-saving effect to improve the energy-saving level and environmental friendliness of industrial furnaces. SUMMARY
[0005] In view of this, the present application provides a black refractory coating and its preparation method and application. The raw materials of the black refractory coating include perovskite black ceramic, iron-chromium spinel, silicon carbide and refractory cement. The black refractory coating of the present application not only has excellent high-temperature stability and high adhesion, but also can achieve high energy-saving effect, and has low cost, simple preparation process, which effectively makes up for the shortcomings of the prior art.
[0006] In order to achieve the above-mentioned application purposes, the present application provides the following technical solutions: The first aspect of the present application provides a black refractory coating, which comprises perovskite black ceramic, iron-chromium spinel, silicon carbide and refractory cement.
[0007] Compared with the prior art, the present application designs a black refractory coating using perovskite black ceramic, iron-chromium spinel, silicon carbide and refractory cement as the main raw materials. In the high-temperature service environment of industrial furnaces, the application of black refractory coating not only bears the basic heat insulation and protection function, but also directly affects the energy efficiency and service life of the furnace.
[0008] The perovskite black ceramic can significantly enhance the radiation heat transfer efficiency in the furnace, reduce fuel consumption and improve heat utilization rate due to its high infrared emissivity and stable black intrinsic characteristics, and its structural stability ensures long-term service at high temperature without fading or failure. The spinel has a stable AB2O4 crystal structure and excellent thermal shock resistance, and is highly reliable and durable in industrial furnaces with frequent start-stop or long-term continuous operation. The SiC has excellent thermal shock resistance and rapid cooling and heating resistance, and is particularly suitable for metallurgical furnace environments with frequent temperature fluctuations and rapid temperature rise and fall.
[0009] The refractory cement has high temperature structural stability and good construction performance, and has significant advantages in industrial applications. Moreover, the refractory cement can form a dense overall coating when compounded with aggregates or functional fillers, and has excellent wear resistance and erosion resistance, which can resist the impact and erosion of high-temperature flue gas, dust and molten materials on the furnace lining surface. In addition, the refractory cement has good thermal shock resistance and is not easy to crack and fall off under the conditions of frequent start-stop or rapid cooling and heating of the furnace, thereby prolonging the service life of the lining. More importantly, the raw materials are widely available and the cost is moderate, which is economical and sustainable, and has a high cost performance in large-scale industrial furnace applications.
[0010] Preferably, the black refractory coating comprises the following raw material components by mass fraction: 1-5 parts of perovskite black ceramic, 1-5 parts of spinel, 10-35 parts of silicon carbide and 50-80 parts of refractory cement.
[0011] Preferably, the chemical formula of the perovskite black ceramic is La 1-x Sr x MnO3, wherein 0 < x ≤ 0.8.
[0012] Further preferably, the perovskite black ceramic is La 0.2 Sr 0.8 MnO3 or La 0.3 Sr 0.7 MnO3.
[0013] Preferably, the preparation method of the perovskite black ceramic comprises the following steps: S1. According to the designed ratio, the lanthanum source, strontium source and manganese source are weighed and mixed uniformly, an alcohol solvent is added, wet ball milling is performed, drying is performed, sieving is performed, and a mixed material is obtained; S2. The mixed material is heated to 900-1000℃ for primary calcination, and after cooling, secondary ball milling is performed, a binder is added, and compression molding is performed to obtain a primary sintered material; S3, under inert atmosphere, heating the primary sintering material to 1350-1400℃ for secondary calcination to obtain the perovskite type black ceramic.
[0014] Further preferably, in step S1, the mass of the lanthanum source, strontium source and manganese source is 1g:2mL-1g:3mL to the mass of the alcohol solvent.
[0015] Further preferably, in step S1, the lanthanum source is lanthanum carbonate, lanthanum oxide or lanthanum nitrate.
[0016] Further preferably, in step S1, the strontium source is strontium oxide, strontium carbonate or strontium nitrate.
[0017] Further preferably, in step S1, the manganese source is manganese dioxide.
[0018] Further preferably, in step S1, the alcohol solvent is anhydrous ethanol.
[0019] Further preferably, in step S1, the ball-to-material ratio of the wet ball milling is 5:1-8:1, the rotation speed is 300-400rpm, and the time is 8-10h.
[0020] Further preferably, in step S2, the time for the first calcination is 3-4h.
[0021] Further preferably, in step S2, the temperature is raised to 900-1000℃ by programmed temperature raising, and the temperature raising rate is 10-15℃ / min.
[0022] Further preferably, in step S2, the binder is polyvinyl alcohol.
[0023] Further preferably, in step S2, the pressure for the pressure forming is 100-150MPa.
[0024] Further preferably, in step S2, the amount of the binder is 3%-5% of the mass of the mixed material.
[0025] Further preferably, in step S2, the rotation speed for the second ball milling is 400-500rpm, and the time is 3-4h.
[0026] Further preferably, in step S3, the temperature is raised to 1350-1400℃ by programmed temperature raising, and the temperature raising rate is 25-30℃ / min.
[0027] Further preferably, in step S3, the time for the secondary calcination is 2-4h.
[0028] The second aspect of the present application provides a preparation method of the black refractory coating, comprising the following steps: weighing each raw material component according to the designed ratio, mixing uniformly, grinding, and obtaining the black refractory coating.
[0029] Preferably, the rotation speed of the grinding is 200-300 rpm, and the grinding time is 15-20 min.
[0030] The third aspect of the present application provides an application of the black refractory coating in the lining of industrial furnaces. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only some of the embodiments of the present application, but not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work fall within the protection scope of the present application.
[0032] Embodiment 1 The embodiment provides a black refractory coating, specifically comprising the following contents: The black refractory coating comprises the following raw material components in mass fraction: La 0.2 Sr 0.8 MnO3 4 parts, iron-chromium spinel 4 parts, silicon carbide 25 parts, and refractory cement 65 parts.
[0033] The preparation method of the black refractory coating is as follows: weighing each raw material component according to the designed ratio, mixing uniformly, grinding at a rotation speed of 250 rpm for 20 min, and obtaining the black refractory coating.
[0034] The La 0.2 Sr 0.8 The preparation method of the La S1, weighing lanthanum oxide, strontium oxide and manganese dioxide according to the designed ratio, mixing uniformly, adding anhydrous ethanol, wet ball milling at a rotation speed of 300 rpm for 10 h, drying at 80℃, and passing through a 200-mesh screen to obtain a mixture; S2, performing first calcination on the mixture at a temperature increasing rate of 15℃ / min to 980℃ for 4 h, cooling, performing second ball milling, the rotation speed of the second ball milling is 450 rpm, ball milling for 3.5 h, adding polyvinyl alcohol with a mass fraction of 4% of the mixture, and adopting a pressure of 120 MPa to perform static pressure molding, and obtaining a first sintered material; S3, performing second calcination on the first sintered material at a temperature increasing rate of 25℃ / min to 1380℃ under an inert atmosphere for 2.5 h, and obtaining the perovskite type black ceramic.
[0035] Embodiment 2 The embodiment provides a black refractory coating, and specifically comprises the following contents. The black refractory coating comprises the following raw material components in mass fractions: La 0.2 Sr 0.8 MnO33 parts, iron-chromium spinel 3 parts, silicon carbide 35 parts and refractory cement 50 parts.
[0036] The preparation method of the black refractory coating is as follows: the raw material components are weighed according to the design ratio, uniformly mixed, and grinded at a rotating speed of 300 rpm for 18 min to obtain the black refractory coating.
[0037] The La 0.2 Sr 0.8 The preparation method of the La S1, lanthanum oxide, strontium oxide and manganese dioxide are weighed according to the design ratio, uniformly mixed, added with anhydrous ethanol, wet ball milled at a ball-to-material ratio of 8:1 and a rotating speed of 350 rpm for 10 h, dried at 80 ℃, and screened through a 200-mesh screen to obtain a mixture; S2, the mixture is heated to 900 ℃ at a heating rate of 15 ℃ / min for primary calcination for 4 h, and then secondarily ball milled at a rotating speed of 400 rpm for 4 h, and polyvinyl alcohol is added in an amount of 4 wt% of the mixture, and the mixture is formed by static pressure molding under a pressure of 120 MPa to obtain a primary sintered material; S3, the primary sintered material is heated to 1375 ℃ at a heating rate of 25 ℃ / min for secondary calcination for 3 h under an inert atmosphere to obtain the perovskite type black ceramic.
[0038] Embodiment 3 The embodiment provides a black refractory coating, and specifically comprises the following contents. The black refractory coating comprises the following raw material components in mass fractions: La 0.3 Sr 0.7 MnO35 parts, iron-chromium spinel 1 part, silicon carbide 20 parts and refractory cement 50 parts.
[0039] The preparation method of the black refractory coating is as follows: the raw material components are weighed according to the design ratio, uniformly mixed, and grinded at a rotating speed of 250 rpm for 20 min to obtain the black refractory coating.
[0040] The La 0.3 Sr 0.7 The preparation method of the La S1, the lanthanum oxide, strontium oxide and manganese dioxide were weighed according to the design ratio, mixed uniformly, added with anhydrous ethanol, wet ball-milled at a ball-to-material ratio of 6:1 and a rotating speed of 400 rpm for 8 h, dried at 80℃, and sieved through a 200-mesh screen to obtain a mixture; S2, the mixture was heated to 980℃ at a heating rate of 15℃ / min for primary calcination for 3.5 h, and then secondary ball-milled at a rotating speed of 450 rpm for 3.5 h, and then added with polyvinyl alcohol at 4wt% of the mass of the mixture, and then formed by static pressure molding at a pressure of 120 MPa to obtain a primary sintered material; S3, the primary sintered material was heated to 1400℃ at a heating rate of 25℃ / min for secondary calcination for 2.5 h under an inert atmosphere to obtain the perovskite-type black ceramic.
[0041] Example 4 The present example provides a black refractory coating, specifically comprising the following contents: The black refractory coating comprises the following raw material components by mass fraction: La 0.2 Sr 0.8 MnO31 part, iron-chromium spinel 5 parts, silicon carbide 35 parts and refractory cement 80 parts.
[0042] The preparation method of the black refractory coating is as follows: the raw material components are weighed according to the design ratio, mixed uniformly, and ground at a rotating speed of 250 rpm for 20 min to obtain the black refractory coating.
[0043] The preparation method of the black refractory coating is as follows: the raw material components are weighed according to the design ratio, mixed uniformly, and ground at a rotating speed of 250 rpm for 20 min to obtain the black refractory coating. 0.2 Sr 0.8 The preparation method of the La S1, the lanthanum oxide, strontium oxide and manganese dioxide were weighed according to the design ratio, mixed uniformly, added with anhydrous ethanol, wet ball-milled at a ball-to-material ratio of 5:1 and a rotating speed of 300 rpm for 10 h, dried at 80℃, and sieved through a 200-mesh screen to obtain a mixture; S2, the mixture was heated to 980℃ at a heating rate of 15℃ / min for primary calcination for 4 h, and then secondary ball-milled at a rotating speed of 450 rpm for 3.5 h, and then added with polyvinyl alcohol at 4wt% of the mass of the mixture, and then formed by static pressure molding at a pressure of 120 MPa to obtain a primary sintered material; S3, the primary sintered material was heated to 1380℃ at a heating rate of 25℃ / min for secondary calcination for 2.5 h under an inert atmosphere to obtain the perovskite-type black ceramic.
[0044] Comparative Example 1 The comparative example 1 provides a black refractory coating, which is different from the example 1 in that the perovskite black ceramic is replaced by an equal amount of ceramic powder, and other ingredients and parameters are unchanged, and specifically includes the following contents: The black refractory coating includes the following mass fractions of raw material components: ceramic powder 4 parts, iron-chromium spinel 4 parts, silicon carbide 25 parts, and refractory cement 65 parts.
[0045] The preparation method of the black refractory coating is as follows: according to the designed ratio, each raw material component is weighed, mixed uniformly, and ground at a speed of 250 rpm for 20 min to obtain the black refractory coating.
[0046] Comparative example 2 The comparative example 1 provides a black refractory coating, which is different from the example 1 in that the perovskite black ceramic is replaced by an equal amount of ceramic powder, and other ingredients and parameters are unchanged, and specifically includes the following contents: The black refractory coating includes the following mass fractions of raw material components: La 0.2 Sr 0.8 MnO3 4 parts, magnesium-aluminum spinel 4 parts, silicon carbide 25 parts, and refractory cement 65 parts.
[0047] The preparation method of the black refractory coating is as follows: according to the designed ratio, each raw material component is weighed, mixed uniformly, and ground at a speed of 250 rpm for 20 min to obtain the black refractory coating.
[0048] The preparation method of the La 0.2 Sr 0.8 MnO3 includes the following steps: S1, according to the designed ratio, lanthanum oxide, strontium oxide and manganese dioxide are weighed, mixed uniformly, added with anhydrous ethanol, wet ball milled at a speed of 300 rpm for 10 h, dried at 80℃, and sieved through a 200 mesh screen to obtain a mixture; S2, the mixture is heated to 980℃ at a heating rate of 15℃ / min for primary calcination for 4 h, and after cooling, secondary ball milling is performed at a speed of 450 rpm for 3.5 h, and polyvinyl alcohol is added at 4wt% of the mass of the mixture, and the mixture is formed by static pressure at a pressure of 120 MPa to obtain a primary sintered material; S3, the primary sintered material is heated to 1380℃ at a heating rate of 25℃ / min for secondary calcination for 2.5 h under an inert atmosphere to obtain the perovskite black ceramic.
[0049] In order to further embody the technical effect of the present application, the application performance test is carried out on the black refractory coating obtained in Examples 1-4 and Comparative Examples 1-2, and each black refractory coating is selected to be coated on a refractory substrate consistent with the target furnace, and in this test, high alumina brick test blocks 150 mm × 25 mm × 25 mm are used, the coating thickness is 400 μm, room temperature drying is carried out, and then sintering at 500 ℃ for 5 h is carried out to obtain test materials. Referring to ASTM C1171, the test materials are subjected to a cycle of heating and holding at 1200 ℃ in air atmosphere for 30 min to air cooling, and 25-50 cycles are carried out, and MOR (ASTM C133) and ultrasonic velocity are measured before and after the test. The pass criteria are: ΔMOR or velocity reduction ≤ 20%, no through cracks and spalling on the surface; referring to national standard GB / T 4653-1984, a Japan TSS-5X infrared radiation tester is used to test the normal emissivity of the coating in the range of 2-16 μm; referring to GB / T 10294-2008, a differential scanning calorimeter (DSC) (Germany Netzsch STA449F3) is used to measure the heat capacity Cp. The thermal conductivity of the sample is obtained by using Kelemen formula; the coating adhesion is tested by using the pull-out method, and the reference standard is ASTM D 4541 "Pull-off Strength of Coatings as Determined by Portable Adhesion Tester"; and the test results are shown in Table 1.
[0050] Table 1 Performance test results of the black refractory coating obtained by using each example and comparative example
[0051] The above only describes the preferred embodiments of the present application and should not be used to limit the present application, and any modification, equivalent replacement or improvement made within the spirit and principle of the present application should be included in the protection scope of the present application.
Claims
1. A black refractory coating, characterized in that, The black ceramic includes perovskite, iron-chromium spinel, silicon carbide and refractory cement.
2. The black refractory coating of claim 1, wherein, The black ceramic includes perovskite, iron-chromium spinel, silicon carbide and refractory cement.
3. The black refractory coating according to claim 1 or 2, characterized in that The chemical formula of the perovskite type black ceramic is La 1-x Sr x MnO3, wherein 0 < x ≤ 0.
8.
4. The black refractory coating of claim 3, wherein, The perovskite type black ceramic La 0.2 Sr 0.8 MnO3 or La 0.3 Sr 0.7 MnO3.
5. The black refractory coating according to claim 3 or 4, characterized in that The preparation method of the perovskite black ceramic includes the following steps: S1, according to the design ratio, the lanthanum source, strontium source and manganese source are weighed and mixed uniformly, alcohol solvent is added, wet ball milling is carried out, drying is carried out, sieving is carried out, and the mixed material is obtained; S2, the mixed material is heated to 900-1000℃ for primary calcination, and after cooling, secondary ball milling is carried out, a binder is added, and pressure forming is carried out, and the primary sintered material is obtained; S3, the primary sintered material is heated to 1350-1400℃ for secondary calcination in an inert atmosphere, and the perovskite black ceramic is obtained.
6. The black refractory coating of claim 5, wherein, In step S1, the total mass of the lanthanum source, strontium source and manganese source is 1g:2mL-1g:3mL of the mass of the alcohol solvent; In step S1, the ball-to-material ratio of the wet ball milling is 5:1-8:1, the rotation speed is 300-400rpm, and the time is 8-10h.
7. The black refractory coating of claim 5, wherein, In step S2, the time of the primary calcination is 3-4h; In step S2, the binder is polyvinyl alcohol; In step S2, the amount of the binder is 3%-5% of the mass of the mixed material; In step S2, the rotation speed of the secondary ball milling is 400-500rpm, and the time is 3-4h; In step S3, the time of the secondary calcination is 2-4h.
8. A process for the preparation of a black refractory coating as claimed in any one of claims 1 to 7, characterized in that, The black refractory coating includes the following steps: the raw material components are weighed according to the design ratio, mixed uniformly, and ground, and the black refractory coating is obtained.
9. The method of producing a black refractory coating according to claim 8, wherein The rotation speed of the grinding is 200-300rpm, and the grinding time is 15-20min.
10. The black refractory coating according to any one of claims 1-7 is applied to the inner lining of an industrial furnace.
